The female education and coeducational schooling proposals (19th-20th centuries): the Catholic church as an educational mediator - Soares Almeida, Jane; Regina Boschetti, Vania (Sociedad de Historia de la Educación Latinoamericana y la Universidad Pedagógica y Tecnológica de Colombia, 2018)
The coeducation of the sexes, long discussed since the late nineteenth century in European countries, has had little impact in Brazil. Under the opposition of the Catholic Church, it was defended by the missionary Protestants arrived in 1870. After consolidating in the Catholic countries, religion was decisive for the educational routes with solid bases in the principles of the Church. Portugal and Spain were faithful representatives of this scenario, which shows the close relationship between education and Catholicism. As regards coeducation, covered in some segments by libertarian principles, it was limited by the conservative force until the twentieth century.